TOKOH – TOKOH ULAMA HADIS KONTEMPORER DI INDONESIA DAN DUNIA - Wawan; Ahmad Akram Addin; Muhammad Ali (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
The science of hadith is a key pillar in the treasury of Islamic scholarship. In this context, the presence of contemporary scholars and hadith figures is crucial. They strive to maintain the validity and credibility of hadith through the study of sanad (chain of transmission) and matan (transmission), while simultaneously interpreting and presenting it contextually in accordance with the social and intellectual realities of today's Muslim community. The purpose of this paper is to identify contemporary hadith scholars in the Islamic world and Indonesia and their thoughts. Studying these contemporary hadith figures is crucial not only to commemorate their contributions and work, but also to emulate the methods and approaches they employ in understanding and teaching hadith in the modern era. In this way, the current generation can continue the scientific legacy with a strong foundation and an orientation that aligns with the needs of the Muslim community today and in the future.